A review on pathology, mechanism, and therapy for cerebellum and tremor in Parkinson’s disease - Yuke Zhong; Hang Liu; Guohui Liu; Lili Zhao; Chengcheng Dai; Yi Liang; Juncong Du; Xuan Zhou; Lijuan Mo; Changhong Tan; Xinjie Tan; Fen Deng; et al. (2022)
Abstract Tremor is one of the core symptoms of Parkinson’s disease (PD), but its mechanism is poorly understood. The cerebellum is a growing focus in PD-related researches and is reported to play an important role in tremor in PD. The cerebellum may participate in the modulation of tremor amplitude via cerebello-thalamo-cortical circuits. The cerebellar excitatory projections to the ventral intermediate nucleus of the thalamus may be enhanced due to PD-related changes, including dopaminergic/non-dopaminergic system abnormality, white matter damage, and deep nuclei impairment, which may contribute to dysregulation and resistance to levodopa of tremor. This review summarized the pathological, structural, and functional changes of the cerebellum in PD and discussed the role of the cerebellum in PD-related tremor, aiming to provide an overview of the cerebellum-related mechanism of tremor in PD.